A snake venom-analog peptide that inhibits SARS-CoV-2 and papain-like protease displays antithrombotic activity in mice arterial thrombosis model, without interfering with bleeding time - Nogueira, Ruben Siedlarczyk; Salu, Bruno Ramos; Nardelli, Vinícius Goulart; Bonturi, Camila Ramalho; Pereira, Marina Rodrigues [UNESP]; de Abreu Maffei, Francisco Humberto [UNESP]; Cilli, Eduardo Maffud [UNESP]; Oliva, Maria Luiza Vilela (Springer Nature, 2023)
Background: (p-BthTX-I)2 K, a dimeric analog peptide derived from the C-terminal region of phospholipase A2-like bothropstoxin-I (p-BthTX-I), is resistant to plasma proteolysis and inhibits severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) strains with weak cytotoxic effects. Complications of SARS-CoV-2 infection include vascular problems and increased risk of thrombosis; therefore, studies to identify new drugs for treating SARS-CoV-2 infections that also inhibit thrombosis and minimize the risk of bleeding are required. Objectives: To determine whether (p-BthTX-I)2 K affects the hemostatic system. Methods: Platelet aggregation was induced by collagen, arachidonic acid, and adenosine diphosphate (ADP) in the Chronolog Lumi-aggregometer. The coagulation activity was evaluated by determining activated partial thromboplastin clotting time (aPTT) and prothrombin time (PT) with (p-BthTX-I)2 K (5.0–434.5 µg) or 0.9% NaCl. Arterial thrombosis was induced with a 540 nm laser and 3.5–20 mg kg− 1 Rose Bengal in the carotid artery of male C57BL/6J mice using (p-BthTX-I)2 K. Bleeding time was determined in mouse tails immersed in saline at 37 °C after (p-BthTX-I)2 K (4.0 mg/kg and 8.0 mg/kg) or saline administration. Results: (p-BthTX-I)2 K prolonged the aPTT and PT by blocking kallikrein and FXa-like activities. Moreover, (p-BthTX-I)2 K inhibited ADP-, collagen-, and arachidonic acid-induced platelet aggregation in a dose-dependent manner. Further, low concentrations of (p-BthTX-I)2 K extended the time to artery occlusion by the formed thrombus. However, (p-BthTX-I)2 K did not prolong the bleeding time in the mouse model of arterial thrombosis. Conclusion: These results demonstrate the antithrombotic activity of the peptide (p-BthTX-I)2 K possibly by kallikrein inhibition, suggesting its strong biotechnological potential.
Keywords: Bleeding; COVID-19; Cysteine-protease; Papain-like protease; Platelets; SARS-CoV-2; Thrombosis